Cytomegalovirus Infection in Kidney Transplant patients. (July 2018) - Siddiqu, Wasim A; Al Salmi, Issa; Jha, Amitabh; Pakkyara, Abbas; Yasir, Mohammad; Shaheen, Faisal A
Abstract : Background: Cytomegalovirus (CMV) is one of the most frequently encountered opportunistic viral pathogens in kidney transplant recipient. The incidence of organ involvements and clinical features are variable among different studies at time of detection of CMV infection. In this study we observed the clinical presentations, hematological and biochemical markers in kidney transplant recipient at various time of CMV infection and its management course. Methods: All cases, from all over the country, with CMV are managed at our centre. We retrospectively reviewed all live related and unrelated kidney transplant recipients on regular follow up since January 2006 to June 2015, who were diagnosed to have CMV clinically and confirmed laboratory by DNA PCR (Quantitative RT-PCR). Results: CMV PCR was detected in one hundred and two kidney transplant recipients. Of those, 79 were live unrelated (commercial) kidney transplant and 23 patients with live related kidney transplant. The median time of detection of CMV infection after kidney transplant was 21 months, ranging from 15 days to 84 months. There were 58 male and 44 female patients. The median age at the time of kidney transplant was 42 years, ranging from 8 years to 80 years. The induction immunosuppression in live related kidney transplants was essentially with Antilymphocyte globulin (ATG) or Anti CD 25 (Basiliximab) while the most common maintenance immunosuppressive regimen was Cyclosporine (CsA), Mycophenolate Mofetil and Prednisolone. Most of the transplant recipients at the time of detection of CMV PCR were asymptomatic (67%). Fever, mainly a low grade was the main presentation in 16 % patients. 15 % of patients presented with diarrhoea and 2% of patients with pneumonitis. Most common hematological abnormality was lymphopenia in 46% of patients, then anemia in 40% and thrombocytopenia in 14% of the patients. The biochemical abnormalities found were elevated ALT in 18% of patients and hyperbilirubinemia in 9% of patients. The serum creatinine was found to be above baseline values in 72% of patients. All patients with CMV infections were treated with intravenous Ganciclovir, 2.5–5 mg/kg q 12 hourly according to creatinine clearance for 21 days. All patients were treated successful but two patients died during the treatment period. There was a significant improvement in the kidney and liver functions after successful treatment of CMV infection. Conclusion: CMV infection in a kidney transplant recipient is mostly asymptomatic. However it should be considered in a patient presenting with unexplained rise in serum creatinine, low grade fever, diarrhoea or unexplained anaemia. A significant improvement in kidney and liver functions along with a rise in haemoglobin was observed upon successful treatment of the CMV infection.